2014
DOI: 10.3357/asem.3847.2014
|View full text |Cite
|
Sign up to set email alerts
|

Pilots’ Visual Scan Patterns and Situation Awareness in Flight Operations

Abstract: Eye-tracking devices can aid in capturing pilots' visual scan patterns and SA performance, unlike traditional flight simulators. Therefore, integrating eye-tracking devices into the simulator may be a useful method for promoting SA training in flight operations, and can provide in-depth understanding of the mechanism of visual scan patterns and information processing to improve training effectiveness in aviation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 18 publications
1
33
0
1
Order By: Relevance
“…Lack of visual attention is an indicator of missing SA, which is a known contributing factor in aviation accidents (17). Although there is a debate concerning a 'bottom-up' or 'top-down' approach to visual attention in the eye-tracking research, it was observed that pilots integrated both bottom-up and top-down visual processes based on their experience and salience of information during tactical operations (25) and a bottom-up approach based on observation of the data without predefined theories relating eye movements to cognitive activity (5).…”
Section: Pilots' Attention Distributions Play a Central Role In Cognimentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of visual attention is an indicator of missing SA, which is a known contributing factor in aviation accidents (17). Although there is a debate concerning a 'bottom-up' or 'top-down' approach to visual attention in the eye-tracking research, it was observed that pilots integrated both bottom-up and top-down visual processes based on their experience and salience of information during tactical operations (25) and a bottom-up approach based on observation of the data without predefined theories relating eye movements to cognitive activity (5).…”
Section: Pilots' Attention Distributions Play a Central Role In Cognimentioning
confidence: 99%
“…Therefore, it was suggested that fixation numbers and fixation duration focused on a certain AOIs might indicate where attention is allocated. The numbers of fixations distributed and fixation duration on relevant AOIs can be not only an effective indicator of pilot's expertise level but can also be closely related to a pilot's situational awareness (25). Military pilots operating aircraft during tactical manoeuvers have to identify rapidly and precisely where, or how, to move to the most appropriate position based on the relative dynamic information of a moving target, as pilots have to assess potential risks of intended tactical manoeuvers to gain the most advantageous dynamic positions by projecting the trajectory movement in the near future.…”
Section: Expert Pilots Have Been Shown To Have a Longer Duration Of Fmentioning
confidence: 99%
“…Thus, it provides a new perspective for studying SA and is favored by many SA researchers. For example, in the field of pilot SA research, Merwe et al [21] used fixation rates and dwell times as "Level 1 SA" indicators and scanning entropy as a "Level 3 SA" indicator to measure pilot SA; Yu et al [22] conducted an eye movement otherness research on military pilots with different SA levels, including pupil sizes and average fixation duration; and through a fighter aircraft simulation experiment, Liu and Su [23] proved that the superiority of eye tracking in measuring pilots' SA lies in having more extensive differences in sensitivity. In the research on controllers' SA, Hyun et al [24] studied the SA differences between novice and expert controllers by using eye movement measures and a thinking-aloud experiment.…”
Section: State Of the Artmentioning
confidence: 99%
“…To this purpose, many previous studies have advocated the use of eye tracking tools, applied mostly in simulated flight scenarios (Blascheck, et al, 2014;Lijing, Hongpeng, Dayong, & Xiuly, 2015;US Department of Transportation FAA, 2012). Some of these studies analyzed the pilots' visual scanning strategies for different flight scenarios and for various pilot categories (Diaz, Cees, Dyer, & Garcia, 2017;Lijing, Hongpeng, Dayong, & Xiuly, 2015;Robinski & Stein, 2013;Yu, Wang, Li, Braithwaite, & Greaves, 2016;Yu, Wang, Li, & Braithwaite, 2014).…”
Section: Introductionmentioning
confidence: 99%